Multiple-component covalent organic frameworks - Ning Huang (Nature Portfolio, 2016)
Covalent organic frameworks are crystalline porous polymers integrating molecular building blocks into periodic structures. Here, the authors report a general multiple-component condensation strategy that enables the use of one knot and two or three linkers to synthesize complex, anisotropic frameworks.